PREVALENCE OF FATIGUE IN ELDERLY POST-STROKE PATIENTS - Vu, Thi Thanh Huyen; Tran, Thi Ha; Tran, Viet Luc (Tạp chí Sinh lý học Việt Nam, 2023)
Objectives: This study aims to describe the prevalence of fatigue in elderly post-stroke patients. Methods: A cross-sectional study included 157 subjects diagnosed with stroke (according to WHO criteria) who were treated as inpatients and outpatients at the National Geriatric Hospital. Participants were aged ≥60 years and were examined or treated at the National Geriatric Hospital from July to November 2021. Data were collected using designed tools that included patient characteristics. The data were entered into REDCap and analyzed using SPSS version 22.0. Results: The mean age of the patients was 73.49 ± 9.58 years, and the female-to-male ratio was 0.89. The proportion of independent patients was 42.7% (n=67), while 57.3% (n=90) were dependent, including 10.2% (n=16) minimally dependent, 14.0% (n=22) partially dependent, 14.6% (n=23) very dependent, and 18.5% (n=29) totally dependent. Sleep disturbances were present in 81.5% (n=128) of participants, which was more than four times the proportion of patients with good sleep quality (18.5%, n=29). The total Fatigue Severity Scale (FSS) score ranged from 7 to 63, with a mean score of 42.32 ± 11.50. The majority of participants (74.5%) had post-stroke fatigue (FSS ≥36 points), nearly three times the proportion of the normal group (25.5%). Most patients agreed that fatigue affected their motor function and that they were prone to fatigue, although they did not consider it a permanent problem. Conclusion: Early detection of fatigue through the FSS screening test in elderly post-stroke patients, followed by appropriate treatment, may help improve treatment effectiveness as well as patients’ quality of life.